A New Kind of Church: The Religious Media Conglomerate as a "Denomination". Issue 3 (2nd October 2018) - Ward, Mark
ABSTRACT: Media deregulation has caused ownership concentration and consolidation across all media industries. The "electronic church" has also developed the oligopolistic structure typical of media industries, resulting in vertically integrated religious media conglomerates with interests beyond broadcasting. Salem Media Group, since 1999 a publicly traded corporation, has not only established itself as the dominant player but also acquired or developed businesses that provide goods and services to evangelical Christians and churches in every area of religious life. The present study argues Salem may be analyzed as a "denomination" for evangelicals. Using Chaves's model of denominations as dual-structure organizations with an agency structure and a religious authority structure, the study sets forth Salem's agency structure and demonstrates how the conglomerate legitimates its control of religious goods by deploying the language of the supernatural. Thus, the study offers a method to analyze the religious media conglomerate as a new organizational form.